601. Prescription Drug Misuse in an HIV-Infected US Military Cohort. (26th November 2018) - Deiss, Robert; Byrne, Morgan; Larson, Derek; Ganesan, Anuradha; Noiman, Adi; Garges, Eric; Randell, Kelli; Okulicz, Jason; Kronmann, Karl; Schofield, Christina; Macalino, Grace; Maves, Ryan; et al.
Abstract: Backgrounds: Prescription drug misuse (PDM) has markedly increased over the last decade and is a significant contributor to the national opioid epidemic. HIV+ individuals are particularly vulnerable to PDM as they experience high levels of chronic pain, anxiety and depression. We examined the prevalence of PDM and associated risk factors among HIV-infected subjects in our cohort. Methods: The US Military HIV Natural History Study (NHS) is comprised of HIV+ active duty, retired military personnel and dependents. Since 2014, participants have completed a computerized behavioral survey regarding patterns of drug use and sexual behavior. We specifically queried topics including use of narcotics, benzodiazepines or stimulants without a prescription or use of medications not as prescribed. Logistic regression was used to compare those reporting and not reporting a lifetime history of PDM. Analyses used anonymous data. Results: Among 1, 558 respondents, 292 (18.7%) reported a history of PDM. The median age of individuals reporting history of PDM was 45 years (interquartile range [IQR] 31–53) compared with individuals without PDM (41 years; IQR 29–35; P = 0.049); the groups did not differ by race, CD4 count or viral load. The prevalence of lifetime PDM was highest among dependent individuals (31.8%), compared with retired (20.6%) or active-duty personnel (15.9%; P = 0.003 for comparison). After adjusting for age and duty status, military officers were significantly less likely to report PDM than enlisted personnel (OR 0.51; IQR 0.31–0.85). Those with a history of PDM were more likely to consume ≥3 alcoholic drinks/day (OR 1.9; IQR 1.4–2.5). In a sub-analysis of active-duty personnel only (median age 30 years), individuals reporting a history of PDM had fewer years since HIV diagnosis (median 2.9 years vs. 3.9 years, P = 0.019). Conclusion: We found prevalent PDM among HIV-infected military personnel and beneficiaries, and PDM was associated with at-risk drinking. This is the first estimate of PDM among HIV+ active-duty personnel, and longitudinal studies in similar cohorts will be useful in further characterizing the epidemiology of PDM. The higher prevalence among recently diagnosed active-duty personnel may suggest an increasing scope of PDM in this group, and interventions to decrease PDM are urgently needed. Disclosures: All authors: No reported disclosures.